2022
DOI: 10.1088/1674-1137/ac5601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a kaonic meson on the ground-state properties of nuclei *

Abstract: The effects of an additional K− meson on the ground-state properties of nuclei are investigated within an axially-deformed Skyrme-Hartree-Fock approach combined with a Skyrme-type kaon-nucleon interaction. The K− meson increases the binding energies of all nuclei, whereas it affects deformations only for light nuclei without shell closure. The nucleon drip lines are modified due to the strongly attractive K−N interaction. This is attributed to the behavior of the highest-occupied nucleon single-particle levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…This is also decisive for the effect of the hyperon on the proton separation energy, which can better be seen by the precise values listed in Table II. Namely, the proton separation energies for s[000], p[101], p[110] hypernuclei SLy4 (s t2 = 1.000, s b4 = 1.000) 19 Na(+L) 18 Ne(+L)…”
Section: We Begin In Tablementioning
confidence: 99%
See 2 more Smart Citations
“…This is also decisive for the effect of the hyperon on the proton separation energy, which can better be seen by the precise values listed in Table II. Namely, the proton separation energies for s[000], p[101], p[110] hypernuclei SLy4 (s t2 = 1.000, s b4 = 1.000) 19 Na(+L) 18 Ne(+L)…”
Section: We Begin In Tablementioning
confidence: 99%
“…In nuclei with added strangeness, strange particles might also affect the drip lines. Previous studies have shown that the weakly-bound nuclear cores of drip line nuclei might be stabilized by the addition of further strongly-bound particles, and the drip line might even be extended by added hyperons [12][13][14][15][16][17] or kaons [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation